2022
DOI: 10.1002/hsr2.518
|View full text |Cite
|
Sign up to set email alerts
|

Screening of psychiatric disorders in women with high‐risk pregnancy: Accuracy of three psychological tools

Abstract: Purpose This study investigated the optimal cutoff points of three psychological tools for screening psychiatric disorders in women with high‐risk pregnancy. Design and Methods In this cross‐sectional study (N = 155), sensitivity/specificity of the Edinburgh Postnatal Depression Scale (EPDS), the Brief Symptom Inventory 53‐items (BSI‐53), and the BSI‐18 were computed with respect to having a psychiatric diagnosis based on the clinical interview. Results The usual cutoffs (≥13 for EPDS, T‐score of 63 for BSI‐53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…It calculates the GSI 30 . In pregnant women, we defined psychological stress as a GSI score >0.5 for BSI‐18 31 . On the basis of findings of research by Akhavan Abiri et al, 32 the results of validity and reliability of the questionnaire were acceptable in the Iranian population and the Cronbach's α was equal to 0.81.…”
Section: Assessmentsmentioning
confidence: 97%
“…It calculates the GSI 30 . In pregnant women, we defined psychological stress as a GSI score >0.5 for BSI‐18 31 . On the basis of findings of research by Akhavan Abiri et al, 32 the results of validity and reliability of the questionnaire were acceptable in the Iranian population and the Cronbach's α was equal to 0.81.…”
Section: Assessmentsmentioning
confidence: 97%
“…Evidence confirmed that prevalence rates of some mental disorders, such as panic disorders and obsession‐compulsive disorder (OCD), during pregnancy were higher than their lifetime prevalence rates in the general population 4 . An Iranian study conducted on 155 pregnant women with high‐risk pregnancies reported a rate of adjustment disorders at 26.1%, phobia at 14.1%, and GAD at 4.3% 3 . Another study revealed that the prevalence of anxiety symptoms among Iranian pregnant women with low‐risk pregnancies was 25.8% 6…”
Section: Introductionmentioning
confidence: 99%
“…4 An Iranian study conducted on 155 pregnant women with high-risk pregnancies reported a rate of adjustment disorders at 26.1%, phobia at 14.1%, and GAD at 4.3%. 3 Another study revealed that the prevalence of anxiety symptoms among Iranian pregnant women with low-risk pregnancies was 25.8%. 6 PADs are related to negative pregnancy outcomes for mothers, fetuses, and children.…”
Section: Introductionmentioning
confidence: 99%
“…There are many different instruments for the assessment of the different aspects of well-being. However, these instruments were developed based on various approaches to well-being and have various items on the different aspects of well-being [ 22 , 23 ]. and hence, there is no comprehensive instrument or approach for the assessment of all aspects of well-being [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…and hence, there is no comprehensive instrument or approach for the assessment of all aspects of well-being [ 24 ]. Some previous studies considered lack of depression, anxiety, and psychological disorders as well-being and used depression- and anxiety-related instruments for well-being assessment [ 23 , 25 28 ]. Some studies also equated well-being with acceptable physical health and hence, used physical health assessment instruments for well-being assessment [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%